An Important Rural Local Organisation in The Central Maluku - N Soukatta (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 1994)
Rural Local Organization plays an important role in the Central Maluku Society especially in the Lease islands.